Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Stock Identity of Stranded Tamanend's Bottlenose Dolphins ( Tursiops erebennus ) With Evidence of Fisheries Interaction in Virginia, North Carolina, and South Carolina, 1996–2019 - Kim W. Urian; Susan G. Barco; Karen L. Clark; Alex M. Costidis; Paul Doshkov; Marina Piscitelli‐Doshkov; Alexandra L. Epple; Tiffany F. Keenan; William A. McLellan; Wayne E. McFee; D. Ann Pabst; Keith A. Rittmaster; et al. (Marine Mammal Science, 2026)
The complex population structure of Tamanend's bottlenose dolphins ( Tursiops erebennus ) along the U.S. Mid‐Atlantic coast complicates assessment of their bycatch. To improve our understanding of the stock identity of individual dolphins taken as bycatch in this region, we compared images of the dorsal fins of bottlenose dolphins that stranded with evidence of fishery interactions (FI+) to the Mid‐Atlantic Bottlenose Dolphin Catalog (MABDC). We obtained stranding data from NOAA Fisheries for 715 FI+ bottlenose dolphins from Virginia (VA), North Carolina (NC), and South Carolina (SC) from 1996 to 2019; approximately two thirds of these records included dorsal fin images. For records for which images were available, we applied restrictive criteria for image quality and dorsal fin distinctiveness and compared the remaining 145 distinctive FI+ individuals to the MABDC. We matched 18 dolphins to regional catalogs and assigned stock identity to 13 of the matches; two were from migratory coastal stocks and 11 were from small estuarine stocks in NC and SC. Our analysis demonstrates how the risk of bycatch varies across bottlenose dolphin stocks along the Mid‐Atlantic coast, provides an important feedback information loop to stranding responders and researchers studying dolphins in the field, and informs conservation efforts to address bycatch of bottlenose dolphins in this region.

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

Complex population structure revealed using genomic data from Tamanend’s bottlenose dolphins (Tursiops erebennus) - Nicole L. Vollmer; Lynsey A. Wilcox Talbot; Antoinette M. Gorgone; Aleta Hohn; Andrew J. Read; Eric S. Zolman; Patricia E. Rosel (Marine Biology, 2025)
In the waters of North Carolina, on the United States east coast, Tamanend’s bottlenose dolphin ( Tursiops erebennus ) is managed as four stocks, differentiated largely based on photo-identification and satellite telemetry data. Two of the stocks reside primarily within estuarine habitats throughout the year, and two others inhabit coastal waters and make broad scale, migratory movements. The spatio-temporal overlap of these stocks in North Carolina varies seasonally, creating a complicated scenario in which stock boundaries are difficult to identify, and the demographic independence among groups is not well understood. Furthermore, incidental mortality and serious injury of dolphins occurs in several North Carolina fisheries, but the spatio-temporal overlap of the four stocks makes it difficult to assign mortalities and characterize their impact on each stock. To investigate population structure in this complex environment, we obtained biopsy samples from Tamanend’s bottlenose dolphins, and utilized next-generation molecular sequencing to produce a data set of over 6,000 single nucleotide polymorphism markers. Cluster and migration analyses supported the presence of four demographically independent populations. However, the distributions of these populations do not align well with the currently delineated stocks. Instead, our analyses support the existence of three populations in estuarine waters of North Carolina and one inhabiting coastal waters. An improved understanding of the underlying population structure of Tamanend’s bottlenose dolphins in these waters will provide a better characterization of stock distribution and support more accurate assignment of mortality, which is necessary for successful conservation and management of this species.

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

Wastewater surveillance of SARS-CoV-2 and influenza in a dynamic university community: understanding how wastewater measurements correspond to reported cases - Matthew J. Jones; Rukayya Ibrahim; Shirley Clark; Yolanda M. Brooks; Heather E. Preisendanz; Thomas L. Richard; Andrew F. Read; Courtney J. Robinson; Samina Noorali; Michael J. Shreve; Nina L. Dennington; Justin D. Silverman; et al. (Science of The Total Environment, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

First report of pepper ringspot virus on potato (Solanum tuberosum) in South Africa - A. Espach; L. Esterhuizen; N. Africander; S. Thiart; D. A. Read; G. Pietersen (Journal of Plant Pathology, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Havens are a pathway, not an endpoint, for species recovery: A response to Woinarski et al. (2023) - John L. Read; Kev Bradley; Iain J. Gordon; Adrian D. Manning; Linda E. Neaves; April E. Reside; Kiarrah J. Smith; Rick Southgate; Adrian F. Wayne; Andrew R. Weeks; Belinda A. Wilson; Katherine E. Moseby (Biological Conservation, 2023)

A qualitative peptide biomarker approach to identify piscine gelatine in products to support food security - Helen H. Grundy; Carla Soto Quintana; Kristine Korzow Richter; Wendy A. Read; Matthew L. Hutchinson; Antony Stephen Lloyd; James Anthony Donarski (Food Additives & Contaminants: Part A, 2023)

The Effects of a Four-Week Neuromuscular Training Program on Landing Kinematics in Pre- and Post-Peak Height Velocity Male Athletes - Paul J. Read; Jon L. Oliver; Ian J. Dobbs; Megan A. Wong; Nakul Tumkur Anil Kumar; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2021)

The impact of temperature at depth on estimates of thermal habitat for short‐finned pilot whales - Stephanie K. Adamczak; William A. McLellan; Andrew J. Read; Christopher L. P. Wolfe; Lesley H. Thorne (Marine Mammal Science, 2021)
Short‐finned pilot whales ( Globicephala macrorhynchus ) experience dramatic changes in temperature during deep dives, but studies of pilot whale habitat use typically rely solely on surface temperature measurements. We quantified vertically integrated thermal habitat for short‐finned pilot whales using a novel metric, degree‐hours, developed using data from digital acoustic recording tags (DTAGs) deployed off Cape Hatteras along with interpolated temperature profiles at depth from the Met Office Hadley Centre EN4 oceanographic data set. We then compared estimates of thermal habitat calculated from surface waters with estimates of vertically integrated thermal habitat calculated using EN4 data collected along the eastern seaboard of the U.S. to understand how available thermal habitat is influenced by seasonal and spatial variability in water temperature. Estimates of vertically integrated thermal habitat were typically lower than estimates produced using surface temperatures, and the difference was greatest at intermediate latitudes and in warmer seasons, where and when there is a high degree of variability between surface and bottom temperatures. Our work highlights the importance of considering temperature at depth to accurately assess the thermal habitat of deep‐diving marine vertebrates, and presents a means of quantifying thermal habitat that will be useful for understanding the thermal ranges of these species.

Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic - Paul W. Hill; Richard Broughton; Jeremy Bougoure; William Havelange; Kevin K. Newsham; Helen Grant; Daniel V. Murphy; Peta Clode; Soshila Ramayah; Karina A. Marsden; Richard S. Quilliam; Paula Roberts; et al. (Ecology Letters, 2019)
In contrast to the situation in plants inhabiting most of the world’s ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO 2 .

Likely annual calving in the vaquita, Phocoena sinus : A new hope? - Barbara L. Taylor; Randall S. Wells; Paula A. Olson; Robert L. Brownell; Frances M. D. Gulland; Andrew J. Read; Francisco J. Valverde‐Esparza; Oscar H. Ortiz‐García; Diego Ruiz‐Sabio; Armando M. Jaramillo‐Legorreta; Edwyna Nieto‐Garcia; Gustavo Cardenas‐Hinojosa; et al. (Marine Mammal Science, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Survey of Citrus tristeza virus (CTV) diversity in pigmented Citrus x paradisi (Macfad.) (Grapefruit) trees in north-western Argentina - D. A. Read; M. F. Palacios; J. Kleynhans; J. Figueroa; L. Foguet; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Survey of citrus tristeza virus (CTV) strains in Citrus x limon (L) Burm f. (lemon) in Tucumán Province, Argentina - D. A. Read; M. F. Palacios; J. Figueroa; L. Foguet; J. Kleynhans; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Detection of hydrodynamic stimuli by the Florida manatee (Trichechus manatus latirostris) - Joseph C. Gaspard; Gordon B. Bauer; Roger L. Reep; Kimberly Dziuk; LaToshia Read; David A. Mann (Journal of Comparative Physiology A, 2013)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Leptotrichia endocarditis: Report of two cases from the International Collaboration on Endocarditis (ICE) database and review of previous cases - L. B. Caram; J. P. Linefsky; K. M. Read; D. R. Murdoch; T. Lalani; C. W. Woods; L. B. Reller; S. S. Kanj; M. M. Premru; S. Ryan; M. Al-Hegelan; P. Y. Donnio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Identification of MHC class I sequences in Chinese-origin rhesus macaques - Julie A. Karl; Roger W. Wiseman; Kevin J. Campbell; Alex J. Blasky; Austin L. Hughes; Betsy Ferguson; Daniel S. Read; David H. O’Connor (Immunogenetics, 2008)

Comparing Effectiveness of Experimental and Implemented Bycatch Reduction Measures: the Ideal and the Real - T. M. COX; R. L. LEWISON; R. ŽYDELIS; L. B. CROWDER; C. SAFINA; A. J. READ (Conservation Biology, 2007)
Fishers, scientists, and resource managers have made substantial progress in reducing bycatch of sea turtles, seabirds, and marine mammals through physical modifications to fishing gear. Many bycatch‐avoidance measures have been developed and tested successfully in controlled experiments, which have led to regulated implementation of modified or new fishing gear. Nevertheless, successful bycatch experiments may not translate to effective mitigation in commercial fisheries because experimental conditions are relaxed in commercial fishing operations. Such a difference between experimental results and real‐world results with fishing fleets may have serious consequences for management and conservation of protected species taken as bycatch. We evaluated preimplementation experimental measures and postimplementation efficacy from primary and gray literature for three case studies: acoustic pingers that warn marine mammals of the presence of gill nets, turtle excluder devices that reduce bycatch of turtles in trawls, and various measures to reduce seabird bycatch in longlines. Three common themes to successful implementation of bycatch reduction measures are long‐standing collaborations among the fishing industry, scientists, and resource managers; pre‐ and postimplementation monitoring; and compliance via enforcement and incentives.

Representation of spectrotemporal sound information in the ascending auditory pathway - Monty A. Escabí; Heather L. Read (Biological Cybernetics, 2003)

REPRODUCTIVE SEASONALITY OF WESTERN ATLANTIC BOTTLENOSE DOLPHINS OFF NORTH CAROLINA, U.S.A. - Victoria G. Thayer; Andrew J. Read; Ari S. Friedlaender; David R. Colby; Aleta A. Hohn; William A. McLellan; D. Ann Pabst; Jennifer L. Dearolf; Nan I. Bowles; John R. Russell; Keith A. Rittmaster (Marine Mammal Science, 2003)
A bstract We describe reproductive seasonality of bottlenose dolphins in North Carolina (NC), U.S.A., using strandings data from the entire coast of NC and sighting data from Beaufort, NC and by estimating dates of birth of known females. We found a strong peak of neonate strandings in the spring (April‐May), and low levels of neonate strandings in the fall and winter. The distribution of neonate strandings was significantly different from a uniform distribution ( P K = 3.8). We found a unimodal distribution of 282 sightings of neonates with a diffuse peak in the summer. The temporal distribution of sightings of neonates departed significantly from a uniform distribution (P K = 5.1). Estimated birth dates of neonates from known females occurred in May ( n = 6) and June ( n = 4), with a single fall birth. These methods shed light on bottlenose reproductive patterns and underscore the value of using information from multiple types of data. Clarification of bottlenose dolphin reproductive patterns, such as the seasonality of birth, may enhance our understanding of the population structure of this species in the mid‐Atlantic region.

Macrobenthic polychaete assemblages of the continental shelf and upper slope off the west coast of the South Island, New Zealand - P. K. Probert; G. B. Read; S. L. Grove; A. A. Rowden (New Zealand Journal of Marine and Freshwater Research, 2001)
Polychaete assemblages are described from replicate box‐core samples collected in summer 1983 at 18 stations on the continental shelf and upper slope (28–943 m) off the west coast of the South Island, New Zealand, south‐eastern Tasman Sea (c. 41–43°S, 169–172°E). Three main station groupings were identified by multivariate analysis: (1) inner shelf sandy stations characterised by Prionospio australiensis, Aricidea (Acesta) sp., Magelona cf. dakini, Paraprionospio aff. pinnata, Aglaophamus sp., Heteromastus filiformis , and Magelona sp.; (2) middle to outer shelf muddy stations characterised by Levinsenia cf. gracilis, Prionospio australiensis, Paraprionospio coora, Aglaophamus verrilli , and Auchenoplax mesos; and (3) upper slope sandy mud or mud stations characterised by Prionospio ehlersi . A combination of water depth and sediment clay content provided the best correlation with the biotic pattern. Spionidae was the most abundant family (49% of polychaete individuals), which may reflect the scope for opportunistic species in a shelf environment characterised by a high input of terrigenous sediment and episodic upwelling.

Phenylalanine kinetics are associated with tardive dyskinesia in men but not in women - M. A. Richardson; Margaret A. Reilly; Laura L. Read; Cheryl J. Flynn; Raymond F. Suckow; Timothy J. Maher; Istvan Sziraki (Psychopharmacology, 1999)

Branched chain amino acids decrease tardive dyskinesia symptoms - M. A. Richardson; Margaret L. Bevans; Josephine B. Weber; Janet J. Gonzalez; Cheryl J. Flynn; Leora Amira; Laura L. Read; Raymond F. Suckow; Timothy J. Maher (Psychopharmacology, 1999)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)

Assessment of chemical toxicity using mammalian mitochondrial electron transport particles - L. M. Knobeloch; G. A. Blondin; H. W. Read; J. M. Harkin (Archives of Environmental Contamination and Toxicology, 1990)